2019
DOI: 10.1039/c8sc03186j
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the speciation and reactivity of carbon-supported gold nanostructures for catalysed acetylene hydrochlorination

Abstract: Distinct gold nanostructures on activated and nitrogen-doped carbons are evaluated in acetylene hydrochlorination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
139
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(160 citation statements)
references
References 43 publications
18
139
0
Order By: Relevance
“…However, it was worth noting that Au/ACF−H 2 O was superior to the typical aqua regia‐treated catalysts in terms of stability over 15 h. The reason for this superior performance was speculatively based on the influence of surface chemistry and could be the presence of SOGs and pyrrolic N species, which may have served as anchoring sites for Au species on the ACF. Recently, Kaiser et al . reported that N species have a stabilizing effect on single Au atoms, which was consistent with our results.…”
Section: Resultssupporting
confidence: 93%
“…However, it was worth noting that Au/ACF−H 2 O was superior to the typical aqua regia‐treated catalysts in terms of stability over 15 h. The reason for this superior performance was speculatively based on the influence of surface chemistry and could be the presence of SOGs and pyrrolic N species, which may have served as anchoring sites for Au species on the ACF. Recently, Kaiser et al . reported that N species have a stabilizing effect on single Au atoms, which was consistent with our results.…”
Section: Resultssupporting
confidence: 93%
“…Schematic representation of crucial hydrogen evolution steps in protic acidic medium on an extended (111) surface of an fcc metal (b) and a typical [166] SAHC (Pd atoms supported on heptazinic carbon nitride) (c). Coordination environments of successful single atom HER catalyst described in the literature [167][168][169][170][171][172][173].…”
Section: Her At Single Atom Catalystsmentioning
confidence: 99%
“…Perez-Ramirez et al found that Au single atoms hosted on N-doped carbon-derived by the controlled pyrolysis of polyaniline exhibited remarkable stability for acetylene hydrochlorination. 6 In our previous work, we reported that metallic Au nanoparticles exhibited considerable catalytic activity for acetylene hydrochlorination, and the aggregation of Au nanoparticles was another reason for the deactivation of the Aubased catalyst in addition to the reduction of Au(III) or Au(I). 7 Therefore, this study used metallic Au as an active site for acetylene hydrochlorination.…”
Section: Introductionmentioning
confidence: 99%